2022
DOI: 10.1116/6.0001911
|View full text |Cite
|
Sign up to set email alerts
|

Using auxiliary electrochemical working electrodes as probe during contact glow discharge electrolysis: A proof of concept study

Abstract: Plasma in-liquid by means of anodic contact glow discharge electrolysis (aCGDE) is a growing research field allowing the selective modification of the electrode and the electrolyte. The aim of this proof of concept study is to demonstrate that auxiliary electrochemical electrodes placed in the vicinity of the plasma electrode can be modified by aCGDE (ignited at the anode by applying a DC voltage between the driving electrodes). Furthermore, we illustrate in how far such auxiliary electrodes can be used as a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…We suggested that the Au oxide is reduced by H 2 O 2 which forms during anodic contact glow discharge electrolysis (aCGDE). [37][38][39][40] Our results also indicate that H 2 O 2 might also form at lower voltages (still in the range of a few 100 V) in the normal electrolysis region, as suggested previously. [41] This approach allows preparing samples within a few minutes.…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…We suggested that the Au oxide is reduced by H 2 O 2 which forms during anodic contact glow discharge electrolysis (aCGDE). [37][38][39][40] Our results also indicate that H 2 O 2 might also form at lower voltages (still in the range of a few 100 V) in the normal electrolysis region, as suggested previously. [41] This approach allows preparing samples within a few minutes.…”
Section: Introductionsupporting
confidence: 88%
“…As described above, the Au oxide formed during HV electrolysis is reduced when the electrode is kept in the electrolysis solution after HV electrolysis. It was suggested that the reduction process is caused by H 2 O 2 in the electrolyte [36,40], which forms during HV electrolysis. [38,39,41] The general ability of H 2 O 2 to reduce Au cations is already known in literature and can be explained by using the standard electrochemical potentials.…”
Section: H 2 O 2 Concentration and Temperature Dependencementioning
confidence: 99%
See 2 more Smart Citations
“…The material usually used as an auxiliary electrode is inert. Platinum (Pt) is an electrochemical electrode material widely used due to the optimal benchmark system [17].…”
Section: Resultsmentioning
confidence: 99%